On the Study of Interference Scenario on TV Broadcast and Wireless Systems for Emergency Communication Networks in TVWS (ELEKTRIKA- Journal of Electrical Engineering, 2023)
This paper investigated frequency sharing between primary TV systems (channels 32 and 49) and Emergency Communication Networks (ECNs). The networks to be implemented in the Osogbo axis of Osun State function on a secondary geographical basis, creating no harm to the original licensed primary TV viewers. A minimum separation distance of 41 dB was suggested as the protected contour for the UHF spectrum to oversee the protection of primary TV users for the UHF bands under consideration. The effects of changing the secondary systems' transmitting power, transmission frequency, and antenna height on the service coverage distance were also explored. The performance of the UHF band was evaluated when it was utilized for secondary transmission at both low and high transmitting powers, with the performance criterion being percentage coverage distance. This work complies with the International Telecommunication Union-Radio sector (ITU-R) recommendations of 16 dB for signal-to-noise ratio and 41 dB for signal strength. It can also be deduced from the result that when the transmission power of ECN devices is raised from 40 mW to 4 W, Effective Isotropic Radiated Power (EIRP) is used; it caused a 76.19% reduction in the coverage spacing for TV channels of ECN Network secondary devices. For the White Space Device (WSD) to operate in Temporal mode, the maximum allowable power (4 W) used in spatial mode should be replaced by a 76.19 per cent reduction. Additional sensing margins of 3.76 dB and 4.04 dB for channels 33 and 43 must be added to the FCC threshold limit of -114 dBm criterion for TV white spaces to assure ECN deployment without causing severe interference to TV customers.